2015
DOI: 10.1016/j.earscirev.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the applications of coal fly ash

Abstract: Coal fly ash, an industrial by-product, is derived from coal combustion in thermal power plants. It is one of the most complex anthropogenic materials, and its improper disposal has become an environmental concern and resulted in a waste of recoverable resources. There is a pressing and ongoing need to develop new recycling methods for coal fly ash. The present review first describes the generation, physicochemical properties and hazards of coal fly ash at the global level, and then focuses on its current and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
568
0
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,391 publications
(663 citation statements)
references
References 149 publications
6
568
0
20
Order By: Relevance
“…Fly ash is a familiar materials used as geopolymerized adsorbents. It is a complex and abundant anthropogenic material which by product of coal combustion in thermal power plants [22]. Fly ash is a waste substance that are easily to found and had been reported that could be effective for removal of heavy metals.…”
Section: Geopolymermentioning
confidence: 99%
“…Fly ash is a familiar materials used as geopolymerized adsorbents. It is a complex and abundant anthropogenic material which by product of coal combustion in thermal power plants [22]. Fly ash is a waste substance that are easily to found and had been reported that could be effective for removal of heavy metals.…”
Section: Geopolymermentioning
confidence: 99%
“…However, these compressive strength values were bellow the value found for the control mortar containing Portland cement only. In the other hand, the compressive strength of cement mortars with FA milled for prolonged time exceeded the value of the control mortar at all ages, while the UMFA mortars showed a decrease in the compressive strength bellow the reference value [10,29,30].…”
Section: Cmss-2017mentioning
confidence: 99%
“…The reactive part of fly ash is their amorphous phase which is composed mainly of silicon [8]. When mixed with Portland cement and water, fly ash induces a reaction with the calcium hydroxide released by the hydration of Portland cement to produce calcium-silicate hydrates (CSH) [9][10][11][12][13]. However, there are few limitations of the use of fly ash in cement because of the late pozzolanic reaction that starts only after 7 to 28 days [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The mass of fly ash generated during coal combustion is estimated to be 750 × 10 6 t globally [1,2]. Taking into account the fact that the percentage of fly ash in the total amount of ash generated is 85% [1,3], the total amount of ash generated via coal combustion is around 880 × 10 6 t. Vassilev et al [4] estimated that approximately 476 × 10 6 t of biomass ash is generated via the combustion of biomass. In total, the amount of ash generated globally is around 1.4 × 10 9 t, which is nearly equal to the mass of municipal solid waste generated globally at 1.3 × 10 9 t [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent statistics and recent reviews indicate that the recycling rates of fly ash are significantly higher: 46% in the USA [8], 60% in India [1], and 67% in China [1]. Primary ash recycling methods include cement and concrete production and mine backfilling [1][2][3].…”
Section: Introductionmentioning
confidence: 99%